2020
DOI: 10.20409/berj.2019.158
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Relationships Between Environmental Uncertainty, Business Strategy and Management Control System on Firm Performance

Abstract: The subject of this study is the effects of three way interaction between environmental uncertainty, business strategy and management control system on firm performance. The data from 94 Turkish manufacturing company of 500 top class company is analyzed with the SPSS. The results of multiple regression analysis indicate that higher differentiation strategy, management control system, the three-way interaction between environmental uncertainty, differentiation strategy and management control system and the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
2
13
1
Order By: Relevance
“…This is contrary to our hypothesis, but the finding is not surprising in that Lam and Yeung (2010), Agle et al (2006) and Cannella et al (2008) had similar findings. Our findings do not support the work of Eker and Eker (2019), who reported a positive correlation for the relationship between environmental uncertainty and nonfinancial performance nor does it support James and George’s (2018) contention that there is a significant positive relationship between uncertainty and supply chain performance.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is contrary to our hypothesis, but the finding is not surprising in that Lam and Yeung (2010), Agle et al (2006) and Cannella et al (2008) had similar findings. Our findings do not support the work of Eker and Eker (2019), who reported a positive correlation for the relationship between environmental uncertainty and nonfinancial performance nor does it support James and George’s (2018) contention that there is a significant positive relationship between uncertainty and supply chain performance.…”
Section: Discussioncontrasting
confidence: 99%
“…While Eker and Eker (2019) found a positive correlation between environmental uncertainty and performance and James and George (2018) found support for their hypothesis that as environmental uncertainty increases, supply chain performance increases, from our work one can see that the positive relationship between the two comes from the idea that uncertainty triggers certain firm activities that improve performance (Mukherji and Jukherji (2017).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Such an operating environment is often said to be the business ecosystem (Bhagavatula et al 2017). Eker and Eker (2019) suggested that higher differentiation strategy, management control system, the three-way interaction between environmental uncertainty, differentiation strategy and management control system often lead to higher firm performance. The networking behavior of executives also needs to be tailored to the environmental uncertainty to achieve higher performance (Srivastava et al 2018).…”
Section: Introductionmentioning
confidence: 99%